Sinking of dense North Atlantic waters in a global ocean model: location and controls - Katsman, C.A.; Drijfhout, Sybren; Dijkstra, H.A.; Spall, M.A. (Journal of Geophysical Research: Oceans, 2018)
We investigate the characteristics of the sinking of dense waters in the North Atlantic Ocean that constitute the downwelling limb of the Atlantic Meridional Overturning Circulation (AMOC) as simulated by two global ocean models: an eddy‐permitting model at 1/4° resolution and its coarser 1° counterpart. In line with simple geostrophic considerations, it is shown that the sinking predominantly occurs in a narrow region close to the continental boundary in both model simulations. That is, the regions where convection is deepest do not coincide with regions where most dense waters sink. The amount of near‐boundary sinking that occurs varies regionally. For the 1/4° resolution model, these variations are in quantitative agreement with a relation based on geostrophy and a thermodynamic balance between buoyancy loss and alongshore advection of density, which links the amount of sinking to changes in density along the edge of the North Atlantic Ocean. In the 1° model, the amount and location of sinking appears not to be governed by this simple relation, possibly due to the large impact of overflows and non‐negligible cross‐shore density advection. If this poor representation of the processes governing the sinking of dense waters in the North Atlantic Ocean is a generic feature of such low‐resolution models, the response of the AMOC to changes in climate simulated by this type of models needs to be evaluated with care.